1999
DOI: 10.1038/sj.bjp.0702618
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of desensitization of the β‐adrenoceptor signalling pathway in rat cardiac tissues following chronic isoprenaline infusion

Abstract: 1 This study examined b-adrenoceptor signalling in cardiac tissues following infusion of isoprenaline (400 mg kg 71 h 71) or vehicle to rats for 14 days. 2 Isoprenaline infusion caused marked hypertrophy of atria and ventricles and reduced the resting rate of spontaneously beating right atria and the basal force of left atrial contraction. 3 In spontaneously beating right atria, concentration-response curves to isoprenaline and forskolin were shifted 7.9 and 3.2 fold to the right following treatment whereas re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…However, compared with the experiment situation, where the mice get only one injection of NE, mice living in the cold have a continuous flow of NE stimulating BAT and are therefore capable of producing enough heat to survive the cold. One would speculate that a prolonged exposure to cold (which increases sympathetic outflow) would decrease ␤ 1 -AR levels since continued stimulation of ␤ 1 -ARs in the rat heart results in loss of ␤ 1 -AR numbers and desensitization of the ␤ 1 -AR and also adenylate cyclase pathway (29,31). However, we show in BAT (Fig.…”
Section: Discussioncontrasting
confidence: 52%
“…However, compared with the experiment situation, where the mice get only one injection of NE, mice living in the cold have a continuous flow of NE stimulating BAT and are therefore capable of producing enough heat to survive the cold. One would speculate that a prolonged exposure to cold (which increases sympathetic outflow) would decrease ␤ 1 -AR levels since continued stimulation of ␤ 1 -ARs in the rat heart results in loss of ␤ 1 -AR numbers and desensitization of the ␤ 1 -AR and also adenylate cyclase pathway (29,31). However, we show in BAT (Fig.…”
Section: Discussioncontrasting
confidence: 52%
“…This effect was associated with preserved basal ventricular systolic function and Ca 2+ -induced inotropic responses, as well as unaltered myocardial norepinephrine release. Consistently, reduced inotropic responses to PDE inhibitors and cAMP were found in rat left atrium and papillary muscle [176] as well as isolated rat [197] and guinea-pig [164] cardiac myocytes following chronic "-AR agonist administration. A reduction in contractile effects of IBMX, a non-selective PDE inhibitor, was observed following long-term (5 days) exposure of rat cardiac myocytes to norepinephrine, an effect associated with unchanged PDE cAMP-hydrolyzing activity [198].…”
Section: Contractile Responses To Pde Inhibitorsmentioning
confidence: 52%
“…A high selectivity for PDE3 inhibition seems not to be a prerequisite for PDE inhibitor to exhibit contractile effect since potent inotropic responses could be elicited by agents like theophylline and IBMX which non-selectively inhibit PDE1, PDE2, PDE3 and PDE4 isoenzymes [65,112,163,164,167,176,177]. Likewise, both PDE3 selective and non-selective PDE inhibitors are able to potentiate "-ARmediated inotropic responses [55,163,164,169,178,179].…”
Section: Blockade Of Adenosine Receptorsmentioning
confidence: 93%
“…The present study is the first to suggest that these changes can be attributed directly to sympathetic overactivation and abnormalities in signal transduction, rather than to diffuse myocardial damage and contractile dysfunction. More importantly, some prior studies have demonstrated a reduced inotropic response to 3-isobutyl-1-methylxanthine (IBMX), a nonselective PDE inhibitor, after chronic β-AR activation [18,35]. However, the daily dose of β-AR agonist employed in these studies was approximately 200 times greater than that used in this study, and basal contractile function was not defined [18,35].…”
Section: Discussionmentioning
confidence: 77%
“…More importantly, some prior studies have demonstrated a reduced inotropic response to 3-isobutyl-1-methylxanthine (IBMX), a nonselective PDE inhibitor, after chronic β-AR activation [18,35]. However, the daily dose of β-AR agonist employed in these studies was approximately 200 times greater than that used in this study, and basal contractile function was not defined [18,35]. Hence, the reduced PDE inhibitor responsiveness could be ascribed to generalized cardiac changes secondary to necrotic or apoptotic damage, well known to occur at high doses of β-AR agonists [3,8].…”
Section: Discussionmentioning
confidence: 98%